Investigation on the optimal configuration of sound absorptive material for automotive application - Arif Amsyar Haron (2022)
In urban cities, public transport such as trains and monorail play an important role as one of the main transports used by workers and students as transportation from one place to another. However, the noise made inside the train by its mechanics frequently disturbs the passengers. Where the train's motor, gearbox, and bogie are located beneath, that is where the noise is coming from. Thus, the main objective of this research is to determine and obtain the optimal configuration of the sound absorptive materials for automotive application focusing in trains/monorail. Three specified objectives were set; which are to design the three different thickness of metamaterials and simulate the behavior towards the sound waves produced; to determine the insertion loss in the train at various frequencies when metamaterials are installed and to analysis the effect of the sound absorbing metamaterial based on the simulation performance. Three types of metamaterials were chosen to be fitted underneath the train; aluminium alloy foam, stainless-steel foam and stainless-steel fiber with 1mm, 3mm and 5mm thickness. The train prototype is done by using SolidWorks software, and the simulation study conducted through COMSOL Multiphysics software. Sound pressure level (SPL) before and after the metamaterials were installed are been collected and discussed to compare and determine the best SPL reduction and highest insertion loss. Aluminium alloy foam with 5mm thickness turned to be the most effective materials to be installed with 16% of SPL reduction. It portrays the highest insertion loss in low frequency range. In addition, all metamaterials with 5mm thickness shows the best sound absorbing materials which is parallel to the relationship with greater thickness of sound absorber materials, will results a greater insertion loss and SPL reduction. To sum up, it is a success study as the overall average SPL in train were reduced from 90.4dB to 76.1dB.